Microbiological profiles and prognostic factors of infection mortality in febrile neutropenic children with malignancy - Yuni Astria; Hindra Irawan Satari; Hartono Gunardi; Hikari Ambara Sjakti (Paediatrica Indonesiana, 2021)
Background Post-chemotherapy febrile neutropenia results in high morbidity and mortality in children with malignancy. Many prognostic factors, such as microorganism patterns, as well as the use of antibiotics and antifungals can affect the outcomes. However, limited study is available in Indonesia. Objective To determine the microbial profiles, antibiotic sensitivity, and other factors that influence mortality from febrile neutropenia in pediatric malignancies with infections. Methods This retrospective cohort and descriptive study of 180 children with 252 episodes of neutropenic fever was done in Cipto Mangunkusumo Hospital, Jakarta, between 2015 and 2017. Medical history of possible predictive prognostic factors, including microorganism patterns and antibiotic sensitivity, were recorded. Prognostic factors were analyzed using multivariate logistic regression tests. Results The most common bacteria was Gram-negative (54.5%), while Candida sp. was the most common fungal infection (82.5%). Klebsiella sp. was mainly sensitive to amikacin (85.71%), while Pseudomonas aeruginosa was sensitive to ceftazidime (75%), as well as amikacin and gentamicin (100% sensitivity in combination). Staphylococcus sp. was mainly sensitive to amoxi-clav and ampi-sulbactam (76.9%). Almost all fungal groups were susceptible to fluconazole, ketoconazole, voriconazole (80-100%). Prognostic factors that increased mortality risk were central venous cannulation (RR 1.947; 95%CI 1.114 to 3.402), wasting (RR 1.176; 95%CI 1.044 to 1.325), severe wasting (RR 1.241; 95%CI 0.975 to 1.579), and hematologic malignancies (RR 0.87; 95%CI 0.788 to 0.976). Conclusion Central venous cannulation and wasting are significant prognostic factors of increased mortality in children with febrile neutropenia. Gram negative bacteria along with Candida sp. is the most common pathogen in such condition.